Effect of Psychological Support Therapy on Psychological State, Pain, and Quality of Life of Elderly Patients With Femoral Neck Fracture - Li, Qun; Wang, Yin; Shen, Xiang (Frontiers in Surgery, 2022)
Purpose: To explore the intervention effect of psychological support therapy (PST) on elderly patients with femoral neck fracture. Methods:82 elderly patients with femoral neck fractures admitted to our hospital from July 2020 to June 2021 were selected. Patients were randomly divided into conventional group (n=41) and intervention group (n=41). The conventional group received routine nursing care, The intervention group was given PST on the basis of the conventional group. The joint function, psychological state, pain, quality of life and nursing satisfaction of both groups were observed. Results:Compared with before intervention, Harris hip joint score and GQOL-74 scores of both groups increased after the intervention, and the increase were more obvious in the intervention group (P<0.05). Compared with before intervention, SAS, SDS scores and VAS score in both groups decreased after the intervention, and the decrease were more obvious in the intervention group (P<0.05). The total satisfaction of intervention group (92.68%) was higher than that of conventional group (75.61%) (P<0.05). Conclusion:PST has a certain intervention effect on elderly patients with femoral neck fracture, which can improve psychological state, reduce pain, improve quality of life and improve nursing satisfaction.